Colombians in france: a two way pendular migration (2010)
This article introduces an academically still little-known and studied migrant population, Colombians settled in France. It deals with the characterization of a human group, whose emigration attained a significant dimension since the late nineties, constituting a clear example of the new ways of international mobility, typified by the multifactor motivations of migrants (well-being pursuit, human security, etc.), a population of multiple features. What this research revealed is that the group recognizes itself through the importance of networks in migratory dynamics, women’s weight within the emigration mass and the persistence of strong ties with the home land. This research follows-up the path of Colombians from their home country to France and back from France to their home land, allowing us to conclude on the existence of a pendular migration of Colombians among those physically and symbolically distinct spaces.